Electromagnetic actuated CVT system for vehicle - Rahman, Mohammed Ataur (2011)
The technical advantage of the present invention is that the response of the electromagnetic actuator is swift so the actuator can move both the pulleys at desired distance within fraction of seconds (0.01s) to provide the torque to the driving wheels in any road conditions. The electromagnetic actuated continuously variable transmission system provides more torque and power than traditional transmissions with smooth speed changing, controlling wider-range speed ratio; and reduces the vehicle transmission losses significantly with pulling and pushing the movable sheave of the pulleys in a stroke length of 8 cm within 0.01 s. As soon as the current is supplied to the actuator, the solenoid turns to electromagnet and starts to attract and to repel the plunger of the vehicle.